The Effect of Profitability and Liquidity on Firm Value with Capital Structure as a Moderating Variable - Gautama, Budhi Pamungkas; Asrifah, Cici; Nurhayati, Netti Siska; Miftahuddin, Asep; Perdana, Yoga (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of profitability and liquidity on firm value with capital structure as a moderating variable in companies in the apparel and luxury goods subsector listed on the Indonesia Stock Exchange during the 2018–2022 period. The research methods used are descriptive and verification quantitative methods. Descriptive methods are used to describe firm value, profitability, liquidity, and capital structure. In contrast, verification methods are used to test the effect of independent variables on the dependent variable and the moderating role of capital structure. Data collection is done using secondary data from the company's published financial statements. The results showed that profitability and liquidity positively and significantly influence firm value. High profitability indicates good economic performance and provides a positive signal to investors. In contrast, high liquidity suggests the company's ability to meet short-term obligations and reduce the risk of bankruptcy. In addition, capital structure is found to function as a moderating variable that can strengthen or weaken the effect of profitability and liquidity on firm value. A balanced capital structure between debt and equity can maximize the benefits of profitability and liquidity, while an unbalanced capital structure can reduce these positive effects. This study implies that company management in the apparel and luxury goods subsector needs to optimize profitability and liquidity and manage the capital structure wisely to increase firm value. The findings also support signal, pecking order, and trade-off theories, which emphasize the importance of effective financial management and optimal capital structure. This study contributes to the financial management and corporate strategy literature and offers practical insights for corporate managers and investors in economic decision-making.